Oceanic Effect on Precipitation Development in the Maritime Continent during Anomalously-Wet Dry Seasons in Java - Erma Yulihastin; Muhammad F P; Suaydhi Suaydhi; Iis Sofiati (Indonesian Journal of Geography, 2021)
Anomalous rainfall during the dry season over the tropical region is determined by sea surface temperature (SST) anomalies driven by remote forcing. Anomalous precipitation during the dry season in Java (the so-called "anomalously-wet dry season”) has increased the number of hydrometeorological disasters, with notable events occurring in 2010, 2013, and 2016. Here we analyze anomalously-wet dry seasons in Java from 2000 to 2019 using variables such as precipitation, wind, temperature, outgoing longwave radiation, and SST obtained from the Tropical Rainfall Measuring Mission and ERA5 European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis. This study focuses on anomalously-wet dry seasons in Java during the absence periods of negative phase for the El Niño Southern Oscillation (ENSO) and/or Indian Ocean Dipole (IOD) by identification the main caused. The results show that the contribution of local seas is more significant (37%) in developing anomalously-wet dry seasons than La Niña (33%), the IOD and La Niña combined (17%), and the IOD alone (13%). Local Indonesian seas play a significant role in causing extreme precipitation and spread over the Maritime Continent. We also find that SSTs in the southern Java Sea are sensitive to a negative IOD, but not to La Niña.